Návrh trupu soutěžního modelu letadla - Bednář, Peter (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2019)
Táto bakalárska práca sa zaoberá návrhom trupu súťažného modelu lietadla . Úvod práce zoznamuje čitateľa so študentským tímom Chicken wings a nastávajúcou súťažou Air Cargo Challenge 2019. Nasleduje rešeršná časť jednotlivých typov materiálov a výrobných technológií uhlíkových kompozitov. Druhá časť rešeršnej práce pojednáva o jednotlivých fázach návrhu lietadla a definícii trupu. Praktická časť práce začína štatistickým prehľadom sériovo vyrábaných modelov kategórie F3B a F5J a následným konštrukčným návrhom jednotlivých častí trupu a hmotnostným rozborom modelu. Záver odôvodňuje voľbu jednotlivých parametrov .

This bachelor’s thesis deals with the design of the fuselage of the competing model aircraft. The introduction describes the student team, Chicken Wings, and also explains the upcoming Air Cargo Challenge 2019. Furthermore, the search section lists the individual types of materials and carbon composite manufacturing technologies. The second part of the thesis deals with the individual phases of the aircraft design and the definition of fuselage. Moreover, the practical part of the thesis begins with a statistical overview of mass-produced models F3B and F5J categories and the subsequent design of the individual parts of the fuselage and the mass analysis of the model. The conclusion justifies the choice of individual parameters.
Design of competition model fuselage
Keywords: Air Cargo Challenge 2019; trupu; hmotnostný rozbor; štatistika; Chicken Wings; Air Cargo Challenge 2019; fuselage; weight distribution; statistics; Chicken Wings